All-solid waste alkali-activated cementing material for foam concrete
By using all solid waste alkali in foam concrete to stimulate gelling materials and replace traditional cement clinker, the problems of high energy consumption and large carbon emissions in the production process of traditional foam concrete are solved, the goal of low-carbon buildings has been achieved, and the Mechanical properties and durability of materials.
Patent Information
- Application Number
- CN202411581515.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
The high energy consumption and large carbon emissions in the production process of traditional foam concrete cementitious materials limit their application in the field of low-carbon construction.
All solid waste alkali excitation gelling materials are used to replace cement clinker by using industrial waste such as lithium slag, fly ash, slag, steel slag, and other industrial waste, and combined with excitants such as phosphogypsum and sodium metaaluminate, to carry out alkali excitation reactions to generate Hydrating products improves the mechanical properties of materials.
It significantly reduces energy consumption and carbon emissions in the foam concrete production process, improves the compressive strength, tensile strength and durability of the materials, and reduces the accumulation of industrial waste and environmental hazards.
Smart Images

Figure BDA0005123240190000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of foamed concrete, and more specifically, to a fully solid waste alkali activated cementitious material for foamed concrete. Background Art
[0002] Foam concrete is a lightweight, porous building material with good thermal insulation, sound insulation, fire resistance and other properties. It is widely used in construction engineering and other fields. Due to the large number of bubbles inside, the density of foam concrete is relatively low, generally between 400 and 1600 kg / m 3 Compared with traditional concrete, it is much lighter and is suitable for lightweight filling materials and reducing the weight of buildings. The porous structure of foam concrete gives it excellent sound insulation and thermal insulation properties, and it is often used in wall filling, floor heating insulation, roof insulation and other occasions. Foam concrete is an inorganic material with good fire resistance. Even in high temperature environments, it will not burn or produce toxic gases, so it is often used in buildings with high fire protection requirements. In addition, due to the good fluidity of foam concrete, it is easy to pump and construct, and can be filled into hard-to-reach gaps, making it suitable for structures with complex shapes such as basements and bridges.
[0003] However, the production of traditional foam concrete cementitious materials often relies on a large amount of cement clinker, and the high energy consumption and carbon emissions during the production process limit its wide application in the field of low-carbon construction. The main component of the cementitious material of foam concrete is cement, and the production process of cement clinker requires calcining limestone and other raw materials at a high temperature of about 1450°C. This process itself is extremely energy-intensive and involves a large amount of fuel consumption (such as coal or natural gas), which directly leads to high carbon emissions. In addition, the calcium carbonate in the limestone decomposes into calcium oxide and carbon dioxide at high temperatures, of which carbon dioxide emissions account for a large proportion. According to relevant data, about 0.8-1 tons of carbon dioxide are emitted for every ton of cement clinker produced, making the cement industry one of the industrial fields with the largest carbon dioxide emissions in the world. Therefore, in order to achieve low-carbon sustainable development, it is crucial to reduce energy consumption and carbon emissions in the production process of foam concrete and improve the durability of foam concrete. Summary of the invention
[0004] In order to alleviate the problems of high carbon emissions and high energy consumption of cement-based foam concrete cementitious materials, and at the same time improve the mechanical and durability properties of foam concrete, the present application provides a full-solid waste alkali-activated cementitious material for foam concrete.
[0005] The present application provides a fully solid waste alkali activated cementitious material for foamed concrete using the following technical solution: A fully solid waste alkali-activated cementitious material for foamed concrete, the components of which include, by weight, 10-20 parts of lithium slag; 25-35 parts of fly ash; 35-45 parts of slag; 10-20 parts of steel slag; 3-8 parts of phosphogypsum; and 5-7 parts of an activator; the activator is a mixture of solid sodium metaaluminate, sodium silicate and carbide slag in a mass ratio of (3.5-4.5):1:1, the modulus of the sodium silicate is 1.5; the phosphogypsum is industrial by-product gypsum.
[0006] Traditional foamed concrete mainly relies on cement clinker as a cementitious material, which consumes a lot of energy during the production process and is accompanied by the emission of a large amount of carbon dioxide. By adopting the above technical solution, industrial wastes such as lithium slag, fly ash, slag, and steel slag are used to replace cement, which fundamentally reduces the demand for cement clinker. Since the preparation process of these solid waste materials does not require high-temperature calcination and there is no huge carbon footprint in cement production, the energy consumption and carbon emissions of the entire production process are greatly reduced. The solid waste materials used in this application, such as lithium slag, fly ash, slag and steel slag, are by-products in industrial production, usually require special treatment or landfill, and will bring additional environmental burdens. By using these waste materials as cementitious materials, the accumulation of waste can be effectively reduced and its potential harm to the environment can be avoided. Lithium slag, fly ash, slag and steel slag each have potential chemical activity, especially under the action of alkali activators, the internal components of these materials can react chemically to generate a large amount of secondary hydration products, thereby improving the mechanical properties of foamed concrete such as compressive strength and tensile strength. Phosphogypsum is an industrial by-product gypsum that can not only participate in the hydration reaction, but also adjust the pore structure inside the foamed concrete. By adding phosphogypsum, the number of large pores in the concrete can be reduced and the number of small pores can be increased, thereby improving the impermeability, frost resistance and durability of the foamed concrete. Sodium aluminate, sodium silicate and carbide slag are used as activators. Under alkaline excitation conditions, the aluminosilicate components in the solid waste materials react with the alkaline solution to generate additional hydration products, which form a strong connection with the pore walls, reduce water penetration, and improve the durability of the concrete. In summary, the present application reduces carbon emissions and enables the gel material to achieve excellent mechanical properties by recycling and proportioning solid waste materials.
[0007] Optionally, the lithium slag is ground to a specific surface area of 400-500m 2 / kg, and the 28d activity index was >95%.
[0008] By adopting the above technical solution, the powder can be ground to 400-500m 2 / kg of lithium slag particles become finer, increasing its specific surface area. The higher specific surface area increases its contact surface with the alkaline activator, improving the reaction rate and hydration activity of the lithium slag. After the particles are refined, the sufficiency of the reaction is enhanced, which is conducive to the generation of more cementitious products. The activity index is an indicator to measure the reaction activity of cementitious materials, which indicates the ratio of the strength contribution of lithium slag to standard cement. A 28-day activity index of >95% means that the strength contribution of lithium slag within 28 days is equivalent to that of standard cement. After fine grinding, the hydration reaction of lithium slag can start quickly at an early stage, and a large amount of cementitious products such as CSH gel are generated.
[0009] Optionally, the slag should be ground to a specific surface area of 400-500m 2 / kg, and the 28d activity index was >90%.
[0010] By adopting the above technical solution, the slag is ground to 400-500m 2 / kg, and its 28-day activity index>90%, effectively stimulating the potential activity of slag and significantly improving the mechanical properties and durability of foamed concrete. Through fine grinding, slag can better react with alkali activators to generate a large amount of hydration products such as CSH gel, which improves the strength of the material.
[0011] Optionally, the fly ash should be ground to a specific surface area of 350-450m 2 / kg, and the 28d activity index was >75%.
[0012] By adopting the above technical solution, the fly ash is ground to 350-450m 2 / kg, and ensure that the 28-day activity index is greater than 75%, which not only stimulates the potential activity of fly ash, improves the strength and durability of foam concrete, but also promotes the efficient utilization of industrial waste, with environmental protection and economic benefits.
[0013] Optionally, the steel slag should be ground to a specific surface area of 400-500m 2 / kg, and the 28d activity index was >70%.
[0014] By adopting the above technical solution, the steel slag is ground to 400-500m 2 / kg, and ensure that the 28-day activity index is greater than 70%, which can effectively stimulate its potential activity and significantly improve the early and long-term strength and durability of foamed concrete. At the same time, this technical solution realizes the efficient resource utilization of steel slag, reduces the use of cement, and has good environmental and economic benefits.
[0015] Optionally, the activator is a mixture of slaked lime and sodium carbonate in a mass ratio of (0.8-1.2):1.
[0016] By adopting the above technical solution, a mixture of slaked lime and sodium carbonate with a mass ratio of (0.8-1.2):1 is selected to ensure the synergistic effect of slaked lime and sodium carbonate, balance the supply of calcium ions and carbonate ions, and avoid the adverse effects of excessive or insufficient stimulants. Too much slaked lime may lead to excessive alkalinity, causing material shrinkage or cracking, while excessive sodium carbonate may affect the durability of the material. As relatively cheap and environmentally friendly stimulants, slaked lime and sodium carbonate not only reduce material costs, but also effectively utilize renewable industrial by-products, further promoting resource recycling.
[0017] Optionally, the activator is a mixture of water glass and sodium hydroxide in a mass ratio of (2.7-3.3):1, and the water glass modulus is 1.5.
[0018] By adopting the above technical solution, water glass contains silicon-oxygen bonds and alkaline oxides, which can provide a silicon source for the gelling material, promote the dissolution and reaction of silicates in materials such as fly ash and steel slag, generate CSH-rich gelling products, and enhance the strength of the material. Sodium hydroxide can provide a highly alkaline environment for the excitation system, quickly dissolve the active ingredients in materials such as fly ash and steel slag, and promote them to react with silicate ions and sodium ions in water glass to generate more gelling substances. Mixing water glass and sodium hydroxide in this ratio can balance the supply of silicon source and alkaline environment, ensuring that the activator system has suitable viscosity and reactivity.
[0019] Optionally, the method for preparing the all-solid waste alkali-activated cementitious material for foamed concrete is: Dry each component separately to make the moisture content less than 1.0%; The component particles are refined by a multi-stage grinding process, and then the components are mixed in powder form in proportion for a mixing time of 60-300s to obtain a fully solid waste alkali-activated cementitious material.
[0020] By adopting the above technical solution, the purpose of the drying treatment is to remove excess moisture from the raw materials. Excessive moisture will affect the storage stability and reaction efficiency of the activator. The particles of the raw materials are refined through a multi-stage grinding process, so that the material has a higher specific surface area, which can significantly improve the reactivity and gelling properties of the alkali-activated material. This preparation method uses all solid waste as the main raw material, maximizes the use of industrial waste such as fly ash and steel slag, reduces dependence on natural resources, and promotes the resource utilization of waste. In addition, there is no large amount of energy consumption and pollutant emissions during the preparation process, which is in line with the development trend of green building materials.
[0021] In summary, this application has the following beneficial effects: 1. Since this application uses industrial waste such as lithium slag, fly ash, slag, and steel slag to replace the traditional production method that relies on cement clinker, it fundamentally reduces the demand for cement, reduces energy consumption and carbon emissions. Under the action of the alkali activator, each solid waste material undergoes a chemical reaction to generate hydration products, which improves the compressive strength and structural density. Phosphogypsum adjusts the pore structure to further enhance the impermeability, frost resistance and durability. This method not only reduces waste accumulation and avoids environmental hazards, but also achieves a significant improvement in material performance, with the dual advantages of environmental protection and high efficiency.
[0022] 2. In this application, it is preferred to grind lithium slag, slag, fly ash and steel slag separately to greatly increase the specific surface area, enhance their reactivity with alkali activators, generate more hydration products such as CSH gel, and thus improve the strength of foamed concrete. Among them, the 28-day activity index of lithium slag, slag, fly ash and steel slag reaches >95%, >90%, >75% and >70% respectively, which significantly improves the early and long-term mechanical properties and durability of concrete, and has both environmental protection and economic benefits.
[0023] 3. The method of the present application does not consume a large amount of energy or emit pollutants during the preparation process, which is in line with the development trend of green building materials. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources. Example
[0025] Example 1 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: Raw material preparation: Lithium slag with 28d activity index>95%, industrial waste slag generated in the process of producing lithium carbonate by sulfuric acid method: 15kg; Class I fly ash with 28d activity index > 75%, model BS34465: 30kg; S95 grade slag with 28d activity index>90%: 40kg; First-grade steel slag with 28d activity index >70%, model XF-27: 15kg; Phosphogypsum, an industrial byproduct of wet phosphoric acid leaching: 5 kg; Exciter: 6.5kg; The activator is a mixture of solid sodium aluminate (McLean's reagent S817913), sodium silicate (McLean's reagent S871944) and carbide slag in a ratio of 4:1:1, and the modulus of the sodium silicate is 1.5.
[0026] Lithium slag, fly ash, slag and steel slag are placed in a graded grinder and ground step by step. After each grinding, the particle size of the powder is detected by a particle detection device, and the specific surface area is calculated based on the particle size distribution. The specific surface area of each material should be controlled within the following range: Lithium slag: 400-500m 2 / kg; Fly ash: 350-450m 2 / kg; Slag: 400-500m 2 / kg; Steel slag: 400-500m 2 / kg; The whole solid waste alkali activated cementitious material for foamed concrete is obtained by mixing lithium slag, fly ash, slag, steel slag, phosphogypsum and an activator.
[0027] Example 2 A method for preparing a fully solid waste alkali-activated cementitious material for foamed concrete: The difference from Example 1 is that 10 kg of lithium slag, 25 kg of fly ash, 35 kg of slag, 10 kg of steel slag, 3 kg of phosphogypsum and 5 kg of activator are mixed to obtain a fully solid waste alkali-activated cementitious material for foamed concrete.
[0028] Example 3 A method for preparing a fully solid waste alkali-activated cementitious material for foamed concrete: The difference from Example 1 is that 20 kg of lithium slag, 35 kg of fly ash, 45 kg of slag, 20 kg of steel slag, 8 kg of phosphogypsum and 7 kg of activator are mixed to obtain a fully solid waste alkali-activated cementitious material for foamed concrete.
[0029] Example 4 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: The method is different from Example 1 in that the mass ratio of solid sodium aluminate to sodium silicate in the activator is 3.5:1.
[0030] Example 5 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: The method is different from Example 1 in that the mass ratio of solid sodium aluminate to sodium silicate in the activator is 4.5:1.
[0031] Example 6 A method for preparing a fully solid waste alkali-activated cementitious material for foamed concrete: The method is different from Example 1 in that the activator is a mixture of slaked lime and sodium carbonate in a mass ratio of 0.8:1.
[0032] Example 7 A method for preparing a fully solid waste alkali-activated cementitious material for foamed concrete: The method is different from Example 1 in that the activator is a mixture of slaked lime and sodium carbonate in a mass ratio of 1:1.
[0033] Example 8 A method for preparing a fully solid waste alkali-activated cementitious material for foamed concrete: The method is different from Example 1 in that the activator is a mixture of slaked lime and sodium carbonate in a mass ratio of 1.2:1.
[0034] Example 9 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: The method is different from Example 1 in that the activator is a mixture of water glass and sodium hydroxide in a mass ratio of 2.7:1, and the modulus of the water glass is 1.5.
[0035] Example 10 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: The method is different from Example 1 in that the activator is a mixture of water glass and sodium hydroxide in a mass ratio of 3:1, and the water glass modulus is 1.5.
[0036] Embodiment 11 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: The difference from Example 1 is that the activator is a mixture of water glass and sodium hydroxide in a mass ratio of 3.3:1, and the modulus of the water glass is 1.5.
[0037] Comparative Example Comparative Example 1 A method for preparing a fully solid waste alkali-activated cementitious material for foamed concrete: The difference from Example 1 is that the specific surface area of each material should be controlled within the following range: Lithium slag: 300-400m 2 / kg; Fly ash: 250-350m 2 / kg; Slag: 300-400m 2 / kg; Steel slag: 300-400m 2 / kg.
[0038] Comparative Example 2 A method for preparing a fully solid waste alkali-activated cementitious material for foamed concrete: the method is different from Example 1 in that lithium slag is not added.
[0039] Comparative Example 3 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: the method is different from Example 1 in that no phosphogypsum is added.
[0040] Comparative Example 4 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: the difference from Example 1 is that the mass ratio of solid sodium aluminate and sodium silicate in the activator is 3:1.
[0041] Comparative Example 5 A method for preparing a fully solid waste alkali-activated cementitious material for foam concrete: The method is different from Example 1 in that the mass ratio of solid sodium aluminate to sodium silicate in the activator is 5:1.
[0042] Performance testing Detection Methods Water-binder ratio control: Prepare the foam concrete paste according to a water-binder ratio of 0.6 (i.e., the mass of water is 60% of the mass of the cementitious material). Mix the uniformly mixed solid cementitious material with water and use a forced mixer to stir at high speed for 5 minutes to ensure that the paste is uniform and has no agglomeration. Pour the prepared paste into a standard slump cone and measure its expansion (slump expansion range) to determine the flow properties of the paste. The expansion should usually be controlled between 150-250mm to ensure the construction fluidity of the paste.
[0043] Mix the foam concrete slurry with the foaming agent and stir it with a high-speed mixer for 3-5 minutes to ensure that the foaming agent is evenly dispersed to form a uniform foam structure. Prepare 600 wet density grade foam concrete and pour the evenly stirred foam concrete slurry into the mold to ensure that the pouring process is continuous and uniform to avoid stratification. After pouring, cover with a wet cloth or plastic film to keep the surface moist and prevent shrinkage cracks caused by excessive water loss. The initial curing time is 1-3 days. After removing the covering, place the foam concrete specimen in a standard curing room with the temperature controlled at 20±2℃ and the humidity above 95% for 28 days of curing. After curing, test the 28d compressive strength and thermal conductivity of the foam concrete.
[0044] Table 1 Test data Combining Example 1 and Comparative Example 1 with Table 1, it can be seen that a higher specific surface area increases the contact surface with the alkaline activator, thereby increasing the reaction rate and hydration activity of the solid waste material. After the particles are refined, the sufficiency of the reaction is enhanced, which is conducive to generating more gelled products, improving the structural density of the material, and achieving higher strength. Due to the increase in specific surface area, the thermal insulation performance will be further improved, while the slump will decrease.
[0045] It can be seen from Example 1 and Comparative Examples 2-4 and Table 1 that the addition of lithium slag can significantly improve the mechanical properties of foamed concrete, such as compressive strength and tensile strength. This is mainly because the active ingredients in the lithium slag can undergo chemical reactions under the action of an alkali activator to generate a large amount of hydration products, which can effectively fill the pores inside the concrete, thereby improving the compactness and strength of the concrete. The addition of phosphogypsum can effectively adjust the pore structure of foamed concrete. By controlling the dosage of phosphogypsum, the number of macropores in the concrete can be reduced, the proportion of small pores can be increased, and the concrete can be made denser. The addition of phosphogypsum can also improve the thermal insulation performance of foamed concrete, making the concrete perform well in terms of heat preservation and insulation. In addition, the addition of phosphogypsum can also improve the water resistance, corrosion resistance and other properties of concrete. A mixture of solid sodium aluminate, sodium silicate and carbide slag with a mass ratio of (3.5-4.5): 1 is selected as an activator to jointly stimulate the potential active ingredients in solid waste materials. This synergistic effect enables solid waste materials to participate more fully in the hydration reaction and generate more hydration products. The ratio of the activator can affect the pore structure of the foamed concrete, refine the pore size distribution of the concrete, reduce the number of large pores and increase the proportion of small pores, thereby improving the strength and thermal insulation properties.
[0046] It can be seen from Examples 1-3 and Table 1 that, through precise proportioning, these solid waste materials can undergo sufficient chemical reactions under the action of the alkali activator to generate a large amount of hydration products, thereby improving the mechanical properties and thermal insulation capabilities of the concrete.
[0047] Combining Example 1 and Examples 4-11 with Table 1, it can be seen that, using an activator, under alkali activation conditions, the aluminum silicate component in the solid waste material reacts with the alkaline solution to generate additional hydration products, which form a strong connection with the pore wall, reduce water penetration, and improve the mechanical properties of concrete. The alkali activator component used in this application is relatively cheap and environmentally friendly, which not only enables the foam concrete to achieve good mechanical and thermal insulation properties, but also effectively utilizes renewable industrial by-products, further promoting resource recycling.
[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A fully solid waste alkali activated cementitious material for foamed concrete, characterized in that: Its components include 10-20 parts of lithium slag, 25-35 parts of fly ash, 35-45 parts of slag, 10-20 parts of steel slag, 3-8 parts of phosphogypsum and 5-7 parts of activator by weight; the activator is a mixture of solid sodium aluminate, sodium silicate and carbide slag in a mass ratio of (3.5-4.5):1:1, and the modulus of sodium silicate is 1.5; the phosphogypsum is industrial by-product gypsum.
2. The all-solid waste alkali-activated cementitious material for foamed concrete according to claim 1, characterized in that: The specific surface area of the lithium slag is ground to 400-500m 2 / kg, and the 28d activity index was >95%.
3. The all-solid waste alkali-activated cementitious material for foamed concrete according to claim 1, characterized in that: The slag should be ground to a specific surface area of 400-500m 2 / kg, and the 28d activity index was >90%.
4. The all-solid waste alkali-activated cementitious material for foamed concrete according to claim 1, characterized in that: The fly ash should be ground to a specific surface area of 350-450m 2 / kg, and the 28d activity index was >75%.
5. The all-solid waste alkali-activated cementitious material for foamed concrete according to claim 1, characterized in that: The steel slag should be ground to a specific surface area of 400-500m 2 / kg, and the 28d activity index was >70%.
6. The all-solid waste alkali-activated cementitious material for foamed concrete according to claim 1, characterized in that: The activator is a mixture of slaked lime and sodium carbonate in a mass ratio of (0.8-1.2):
1.
7. The all-solid waste alkali-activated cementitious material for foamed concrete according to claim 1, characterized in that: The activator is a mixture of water glass and sodium hydroxide in a mass ratio of (2.7-3.3):1, and the modulus of the water glass is 1.
5.
8. The all-solid waste alkali-activated cementitious material for foamed concrete according to any one of claims 1 to 7, characterized in that: The preparation method of the all-solid waste alkali-activated cementitious material for foam concrete is as follows: Each component is dried separately to make the moisture content less than 1.0%; The component particles are refined by a multi-stage grinding process, and then the components are mixed in powder form in proportion for a mixing time of 60-300s to obtain a fully solid waste alkali-activated cementitious material.
Citation Information
Cited By
Solid waste-based cementing material and preparation method thereof
CN120136464A